Quantitative Assessment of Pericardial Delayed Hyperenhancement Predicts Clinical Improvement in Patients With Constrictive Pericarditis Treated With Anti-Inflammatory Therapy. (May 2015) - Cremer, Paul C.; Tariq, Muhammad U.; Karwa, Abhishek; Alraies, M. Chadi; Benatti, Rodolfo; Schuster, Andres; Agarwal, Shikhar; Flamm, Scott D.; Kwon, Deborah H.; Klein, Allan L.
<x xml:space="preserve">Abstract</x> Background— Delayed hyperenhancement (DHE) of the pericardium usually represents ongoing inflammation and may identify patients with constrictive pericarditis that will improve with anti-inflammatory therapy. However, a quantitative assessment of pericardial DHE has not been performed, and the hierarchical relationship among clinical factors, inflammatory markers, and pericardial DHE is unknown. Methods and Results— We identified 41 consecutive patients with constrictive pericarditis who had a cardiovascular magnetic resonance study with DHE prior to the initiation of anti-inflammatory medications. Pericardial inflammation was quantified on short-axis DHE sequences by contouring the pericardium, selecting normal septal myocardium as a reference region, and then quantifying the pericardial signal that was >6 SD above the reference. Our primary outcome was clinical improvement with anti-inflammatory therapy. The mean age of our patients was 58 years, most patients were male (83%) with New York Heart Association Class II or III (59%) heart failure, and the median follow-up was 1 year. Chest pain, lower New York Heart Association class, higher Westergren sedimentation rates, and increased pericardial DHE were all significantly associated with clinical improvement (P<0.01 for all). When quantitative pericardial DHE was added to a model that included age, chest pain, New York Heart Association class, and Westergren sedimentation rates, the global χ2 improved significantly (P=0.04 for DHE), and the area under the receiver operating characteristic curve was 0.96. Conclusions— In patients with constrictive pericarditis treated with anti-inflammatory therapy, a quantitative assessment of pericardial DHE can provide incremental information to predict clinical improvement when added to clinical factors and Westergren sedimentation rates.